Mastering VBA for Microsoft Office 2010 - Mansfield, Richard, 1945-; Safari eBooks (Indianapolis, Ind. : Wiley Pub., 2010)
"Visual Basic for Applications (VBA) is the language used for writing macros, automating Office applications, and creating custom applications in Word, Excel, PowerPoint, Outlook, and Access. This complete guide shows both IT professionals and novice developers how to master VBA in order to customize the entire Office suite for specific business needs."--Resource description page.
Description based on print version record.
Includes index.
Keywords: Microsoft Visual Basic for applications; Microsoft Office; Electronic books